Analisis Kedisiplin Guru Terhadap Karakter Peserta Didik di UPTD SD GMIT Paliboo - Hana L. Atmalai; Jon A. Lalang Yame; Depopamia Laupada; Dina M. Maukari; Herlina Batang; Hana B. Djenmakal (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Education is actually a funnel for making life better and more focused. This means that education stops humans from achieving the highest human qualities possible. Discipline does not only apply to students, but discipline also applies to teachers, every teacher must comply with the rules made by the school and be responsible for their duties. Teacher discipline greatly influences the character of students because if the teacher lacks discipline in learning, students will follow what the teacher does. This research aims to determine teacher discipline towards the character of students at GMIT Paliboo Elementary School which is located on Jl. Soekarno Hatta. Paliboo, Kabola District, Alor Regency, East Nusa Tenggara Province, this data was taken by researchers during the internship process at school for 8 meetings. The research method used is descriptive qualitative. Based on the results of observations and interviews, there are still some teachers who are often late and therefore pay less attention to students. Likewise, researchers examined the condition of students at SD GMIT Paliboo, there were still many students who were late, often fought teachers, often bullied, and came in and out of class during learning hours.